1992
DOI: 10.1017/s0022143000009655
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of borehole-inclinometer data: a general theory applied to a new instrument

Abstract: Borehole inclinometers are standard equipment for field glaciologists and are commonly used for investigating the flow law of ice and for measuring the spatial position of englacial and sub-surface sensors. The recent development, at the University of British Columbia (UBC), of a prototype inclinometer that employs a three-component fluxgate magentometer to obtain a compass bearing has stimulated our interest in borehole inclinometry. Following a review of various approaches to glacier inclinometry, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, Blake and Clarke (1992) demonstrated that inclinometry may underestimate borehole tilt due to tension in the inclinometer cable, which tends to pull the top of the instrument into a more vertical orientation than the hole itself. As a result, inclinometry data provided minimum estimates of internal ice deformation and therefore yielded maximum estimates of basal velocities.…”
Section: Field Methodsmentioning
confidence: 99%
“…However, Blake and Clarke (1992) demonstrated that inclinometry may underestimate borehole tilt due to tension in the inclinometer cable, which tends to pull the top of the instrument into a more vertical orientation than the hole itself. As a result, inclinometry data provided minimum estimates of internal ice deformation and therefore yielded maximum estimates of basal velocities.…”
Section: Field Methodsmentioning
confidence: 99%
“…Inclinometer measurements give information on the flow field deforming the borehole axis (Hooke and others, 1987;Hubbard and others, 1998). A historical overview of different aspects of inclinometry is given by Blake and Clarke (1992).…”
Section: Introductionmentioning
confidence: 99%
“…and Clarke [1992], and therefore can lead to overestimates of basal slip velocity. Therefore, in driving the finite element model, we begin by considering end-member scenarios for input velocities in which slidometer data give minimum basal velocities and inclinometer data give maximum basal velocities, as illustrated in Figure 4.16.…”
Section: Model Resultsmentioning
confidence: 99%
“…However, the method, when used in uncased boreholes, has larger, additional sources of error [Blake and Clarke, 1992;Harper et al, 2001]. Blake and Clarke [1992] demonstrated that inclinometry tends to underestimate borehole tilt due to tension in the inclinometer cable, which tends to pull the top of the instrument into a more vertical orientation than the hole…”
Section: Field Methodsmentioning
confidence: 99%
See 1 more Smart Citation